A chip-based immunoaffinity capillary electrophoresis assay for assessing hormones in human biological fluids - Wellner, Edward F. (2008)
A chip-based capillary electrophoresis system has been designed for assessing the concentrations of four hormones in whole human blood, saliva, and urine. The desired analytes were isolated by immunoextraction using a panel of four analyte-specific antibodies immobilized onto a glass fiber insert within the injection port of the chip. Following extraction, the captured analytes were labeled prior to electro-elution into the chip separation channel, where they were resolved into four individual peaks in circa 2 min. Quantification of each peak was achieved by on-line LIF detection and integration of the area under each peak. Comparison to commercial high-sensitivity immunoassays demonstrated that the chip-based assay provided fast, accurate, and precise measurements for the analytes under investigation. As the availability of commercially available antibodies rapidly expands, the application of this system will greatly increase. Chip-based CE separations of multiple analytes from a single sample also provide a significant advantage in the analysis of small samples.